Currency futures - Coyle, Brian; The Chartered Institute of Bankers (Chicago, Ill. : Glenlake Pub. Co. ; New York : Fitzroy Dearborn, 2000)
As the foreign exchange markets have developed and grown so more sophiscated financial instruments have been devised. This book is a practical introduction to futures, options and the futures market as a whole. It explains how the markets operate and unravels a futures contract piece by piece to illustrate its purpose, structure and the obligations of the parties involved. Finally it considers the criteria that a company must consider before deciding to use currency futures.
Includes index.
oif 17/07/14
Loan
Keywords: Financial futures; Foreign exchange futures